Synthesis of minimally restrictive optimal stability-enforcing supervisors for nondeterministic discrete event systems - Han, Xiaoguang (2020)
In this paper, we investigate stability-enforcing supervisory control of nondeterministic discrete event systems (DESs) from a brand-new angle. First, the dynamics of a discrete event system (DES) are converted into an algebraic equation in the framework of Boolean semi-tensor product. Using it, several necessary and sufficient conditions are presented to verify whether a DES is stable or not. Second, effective verification criteria are provided for the stabilization problem of DESs. Further, a cost function of disabling controllable events at corresponding states is defined. A matrix-based methodology of finding all minimally restrictive optimal stability-enforcing supervisors is presented. Finally, two examples are provided to illustrate the theoretical results.